Uji Efek Antidiabetes Ekstrak Akar Garcinia rostrata Hassk.ex Hook.f Pada Mencit Jantan (Mus musculus) Dengan Metode Toleransi Glukosa Dan Induksi Aloksan - Nifien Mokuna; Ramadhanil Ramadhanil; Yuliet Yuliet (Biology Department, Mathematics and natural science, Tadulako University, 2014)
Traditional medical treatment is one of the ways to lower the glucose level in the blood. It is a plant Garcinia rostrata Hassk.ex Hook.f one of the plants which has a potential to lower the glucose level in blood. This is supported by alkaloid, flavonoid, saponin efficacious as an anti-diabetic. Therefore, hypoglycemia activity of Garcinia rostrata Hassk.ex Hook.f root extract test was conducted by using glucose tolerance and alloxan methods at mice. The objective of this research is to know the hypoglycemia activities of Garcinia rostrata Hassk.ex Hook.f root extract and to know the effective dosage of Garcinia rostrata Hassk.ex Hook.f to lower the glucose in blood of the male mice by utilizing glucose tolerance and alloxan induction method. Garcinia rostrata Hassk.exHook root extract was taken trough reflux method by using 96% ethanol as distillation. In addition, a test by using male mice (Mus musculus) was conducted, where the mice were grouped into five groups, those were controlled glibenclamide positive group, negative control Na CMC 0,5%, dosage 1 (130 mg/Kg BW), dosage 2 (195 mg/kg BW), and dosage 3 (230 mg/Kg BW). The results showed that the root extract of Garcinia rostrata Hassk.ex Hook.f have hypoglycemic activity and effective dose for lowering blood glucose levels in glucose tolerance method is 3 (230 mg / kg bw)doses, while a dose of 1 (130 mg / kg bw) have the effect of lowering blood glucose levels were not significantly different with 2 (195 mg / kg bw) doses and 3 (230 mg / kg bw) doses but it's better than the positive control glibenclamide on alloxan induction method. Keywords: Garcinia rostrata Hassk.ex Hook.f root, glucose tolerance, alloxan induction.